The Cultural Politics of Canadian Land Trusts: Exploring the Ethos and Structureof the Social Economy as Articulated Across Protected Private Lands - Hanson, Lorelei; Filax, Gloria (International Journal of Canadian Studies / Revue internationale d’études canadiennes)

(untitled) (Conseil international d'études canadiennes, 2009)
AbstractThis paper examines the emerging structure and culture of Canadian land trustorganizations that set aside private land for conservation purposes. While a numberof researchers in both the US and Canada have viewed land trusts as privatizedconservation mechanisms, a closer examination of their social, economic andecological objectives demonstrates that land trusts inhabit the space between thepublic and private sector in a manner characteristic of social economyorganizations. However, a comparison of the structure and ethos of the Canadian landtrust movement to the ideals embraced by the social economy sector reveals thatwhile land trusts have many of the foundational elements of the social economy, theyneed to engage more consciously and broadly with civil society if they are to fullyfulfill their conservation and social mandates.